“Lansia Berdaya” Program Penguatan Posyandu Lansia Dusun 2 Desa Karangwuni Sebagai Upaya Peningkatan Pengetahuan dan Pencegahan Hipertensi - Mulyani Adi Astutiatmaja; Very Rizkia Dewiyanti; Qulbiyani Rukmana; Amalia Sianty; Filsa Shintya Ainaya; Afifah Nurhafni Ayati; Kirana Haura’ Arie Prasastywy; Ma’arif Ardhi Saputro; Andi Subandi; eny fauziana; Dwi Lestari; Izzatul Arifah; Dwi Linna Suswardany (Warta LPM, 2024)
Hypertension, a non-communicable disease, exhibits significant death and suffering rates worldwide, including in Indonesia. Hypertension ranks as the third leading cause of mortality in Indonesia, following strokes and tuberculosis, primarily impacting the older population. Dusun 2 Karangwuni is a region that experiences a high mortality rate due to hypertension. The hypertension screening findings revealed that out of the 49 elderly visitors to Posyandu, 41 of them were found to have hypertension. The team's objective is to implement the dedication of Lansia Berdaya's activities in managing hypertension in Dusun Two village, Karangwuni, Weru district. The Lansia activities occur in Dukuh Ngampas, Dusun 2, Village KarangWuni, district Weru, Sukoharjo. Activities encompass kader upgrading training, hypertension assessment, rehabilitation, and elderly gymnastics. The sequence of events will occur in February 2023. The intended recipients are 17 healthcare professionals, whereas the intended recipients are 47 individuals. Activities are evaluated by examining the level of knowledge, which is determined using pre-test and post-test values.   Heath cadre training was conducted with 17 audiences. Hypertension screening, senior gymnastics, and health education activities were conducted and attended by 47 seniors. The hypertension exercise video has been distributed to the health cadre. The video is anticipated to serve as a comprehensive manual for gymnastics exercises at Posyandu Lansia to establish a long-lasting and sustainable devotion program.